Photovoltaic front sheet and method for producing same, and photovoltaic module and photovoltaic curtain wall
Patent Information
- Application Number
- CN202611145062.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-16
AI Technical Summary
但是,光线在前板玻璃的表面散射,伴随着高光学反射损失,会导致光伏组件的发电量损失严重,无法满足兼顾高装饰性与高发电效率的需求
[0015] Compared with the prior art, the beneficial effects of this application are as follows: In the photovoltaic front panel and its preparation method, as well as the photovoltaic module and photovoltaic curtain wall provided in the embodiments of this application, the substrate of the photovoltaic front panel is coated with the clay slurry formed by mixing the nano-clay, the thermoplastic resin and the organic solvent on the light-facing side. The clay slurry is dried to form the composite scattering film. Since the nano-clay dispersed in the thermoplastic resin can form a wave network with a three-dimensional refractive index, light undergoes weak Rayleigh/Mie scattering (i.e., volume scattering) inside the composite scattering film, which only changes the direction of the light path to form haze and white appearance, and hardly produces interface reflection and non-absorption loss. Therefore, the white appearance of the photovoltaic front panel can be achieved. Compared with the surface scattering of light on the surface of the traditional photovoltaic front panel, the optical loss caused by optical reflection is reduced, thereby reducing the power generation loss of the photovoltaic module using the photovoltaic front panel, which is conducive to improving the power generation efficiency of the photovoltaic module, so that the photovoltaic module can take into account both high decoration and high power generation efficiency.
Smart Images

Figure CN122934906A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of photovoltaic technology, and in particular to a photovoltaic front panel and its preparation method, as well as photovoltaic modules and photovoltaic curtain walls. Background Technology
[0002] Building Integrated Photovoltaics (BIPV) is a technology that integrates photovoltaic modules into buildings. These modules can be used as building materials such as curtain walls, roofs, and skylights, combining power generation with architectural aesthetics.
[0003] Currently, most technical solutions for achieving a white appearance in photovoltaic modules are designed based on the surface scattering characteristics of the photovoltaic front panel. For example, using high-mesh textured frosted glass or roughened patterned glass as the front panel glass, relying on the microscopic texture of the glass surface to scatter light and achieve a white appearance for the photovoltaic module, is the most common solution in the industry. However, the scattering of light on the surface of the front panel glass, accompanied by high optical reflection loss, leads to significant power generation loss in the photovoltaic module, failing to meet the requirement of balancing high aesthetics and high power generation efficiency. Summary of the Invention
[0004] This application aims to at least solve one of the technical problems existing in the prior art. To this end, embodiments of this application provide a photovoltaic front panel and its preparation method, as well as photovoltaic modules and photovoltaic curtain walls. The substrate of the photovoltaic front panel is coated with a clay slurry formed by mixing nano-clay, thermoplastic resin and organic solvent on the light-facing side. The clay slurry is dried to form a composite scattering film. Light can undergo volume scattering within the composite scattering film, thereby achieving a white appearance for the photovoltaic front panel. Compared with surface scattering of light on the surface of a traditional photovoltaic front panel, this reduces optical loss caused by optical reflection, thereby reducing the power generation loss of the photovoltaic module using the photovoltaic front panel. This is beneficial to improving the power generation efficiency of the photovoltaic module, enabling the photovoltaic module to achieve both high decorative appeal and high power generation efficiency.
[0005] To achieve the above objectives, in a first aspect, embodiments of this application provide a method for preparing a photovoltaic front panel, the method comprising: Nano-clay, thermoplastic resin, and organic solvent are dispersed in a certain proportion to prepare a clay slurry; wherein, in the clay slurry, the volume fraction of the nano-clay is 20% to 80%, the volume fraction of the thermoplastic resin is 15% to 20%, and the balance is the organic solvent. A substrate is provided, and the clay slurry is coated onto the light-facing surface of the substrate; and The substrate coated with the clay slurry is dried to obtain a photovoltaic front panel with a composite scattering film formed on the light-facing surface. The brightness of the composite scattering film is 30 to 60, the haze of the composite scattering film is 35% to 95%, and the transmittance of the composite scattering film is 55% to 90%.
[0006] In one embodiment, the nanoclay has a volume fraction of 25% to 75% in the clay slurry, and the composite scattering film has a thickness of 8 μm to 12 μm.
[0007] In one embodiment, the nano-clay is one or a combination of at least two of montmorillonite, kaolinite, illite, sepiolite, and optically active clay; And / or, the thermoplastic resin is one or a combination of at least two of the following: thermoplastic acrylic resin, polyvinyl chloride, polyether ether ketone, polystyrene, polytetrafluoroethylene, polyether ester, polyurethane, polyvinyl alcohol, polyethylene, polystyrene-butadiene copolymer, polycarbonate, polyvinyl acetal, modified thermoplastic epoxy resin, and polyimide ester. And / or, the organic solvent is a combination of at least two of the following: terpineol, butyl carbitol acetate, butyl carbitol, dibutyl phthalate, benzyl alcohol, diethylene glycol dibutyl ether, diethylene glycol butyl ether, and diethylene glycol butyl ether acetate; And / or, the substrate is one of the following: low-iron ultra-clear glass, float glass, patterned glass, textured glass, ultra-clear tempered glass, ultra-clear semi-tempered glass, and transparent polymer substrate.
[0008] In one embodiment, the nano-clay is organically modified montmorillonite, the thermoplastic resin is weather-resistant thermoplastic acrylic resin, and the organic solvent is a mixture of terpineol and butyl carbitol acetate.
[0009] In one embodiment, the thickness deviation of the composite scattering film in different regions is less than 0.5 micrometers; And / or, the step of coating the clay slurry onto the light-facing surface of the substrate specifically includes: uniformly coating the clay slurry onto the light-facing surface of the substrate using at least one of a spin coater, a slot coater, a spraying device, and a blade coater. And / or, the drying of the substrate coated with the clay slurry specifically includes: allowing the organic solvent in the clay slurry to evaporate naturally under normal temperature and windless conditions until it is dried and cured.
[0010] In one embodiment, before coating the clay slurry onto the light-facing surface of the substrate, the preparation method further includes: using a magnetron sputtering apparatus or an electron beam evaporation apparatus to alternately deposit Nb2O5 and SiO2 on the light-facing surface of the substrate to form a multilayer periodic structure.
[0011] In one embodiment, the total number of Nb2O5 and SiO2 layers is 4 to 10. And / or, using a multi-objective Bayesian optimization algorithm, adjust the thickness of each layer of Nb2O5 and SiO2.
[0012] Secondly, embodiments of this application provide a photovoltaic front panel, which is prepared using the photovoltaic front panel preparation method described in any of the above embodiments.
[0013] Thirdly, embodiments of this application provide a photovoltaic module, including a photovoltaic front panel, a first encapsulating film, a solar cell, a second encapsulating film, and a photovoltaic back panel that are sequentially laminated together. The photovoltaic front panel is prepared using the photovoltaic front panel preparation method described in any of the above embodiments.
[0014] Fourthly, embodiments of this application provide a photovoltaic curtain wall, including the photovoltaic modules described above.
[0015] Compared with the prior art, the beneficial effects of this application are as follows: In the photovoltaic front panel and its preparation method, as well as the photovoltaic module and photovoltaic curtain wall provided in the embodiments of this application, the substrate of the photovoltaic front panel is coated with the clay slurry formed by mixing the nano-clay, the thermoplastic resin and the organic solvent on the light-facing side. The clay slurry is dried to form the composite scattering film. Since the nano-clay dispersed in the thermoplastic resin can form a wave network with a three-dimensional refractive index, light undergoes weak Rayleigh / Mie scattering (i.e., volume scattering) inside the composite scattering film, which only changes the direction of the light path to form haze and white appearance, and hardly produces interface reflection and non-absorption loss. Therefore, the white appearance of the photovoltaic front panel can be achieved. Compared with the surface scattering of light on the surface of the traditional photovoltaic front panel, the optical loss caused by optical reflection is reduced, thereby reducing the power generation loss of the photovoltaic module using the photovoltaic front panel, which is conducive to improving the power generation efficiency of the photovoltaic module, so that the photovoltaic module can take into account both high decoration and high power generation efficiency.
[0016] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description or may be learned by practice of this application. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the implementation will be briefly introduced below. Obviously, the drawings described below are some implementations of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0018] Figure 1 This is a flowchart of a method for preparing a photovoltaic front panel according to one embodiment of this application.
[0019] Figure 2 This is a schematic diagram of the hierarchical structure of a photovoltaic front panel provided in one embodiment of this application.
[0020] Explanation of key figure labels: 100-Photovoltaic module; 1-Photovoltaic front panel; 2-First encapsulation film; 3-Solar cell; 4-Second encapsulation film; 5-Photovoltaic back panel. Detailed Implementation
[0021] The embodiments of this application are described in detail below. Examples of these embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain this application, and should not be construed as limiting this application.
[0022] In related technologies, most solutions for achieving a white appearance for photovoltaic modules are designed based on the surface scattering characteristics of the photovoltaic front panel. For example, using high-mesh textured frosted glass or roughened patterned glass as the front panel glass, relying on the microscopic texture of the glass surface to scatter light and achieve a white appearance for the photovoltaic module, is the most common solution in the industry. However, the scattering of light on the surface of the front panel glass, accompanied by high optical reflection loss, leads to significant power generation loss in the photovoltaic module, failing to meet the requirement of balancing high aesthetics and high power generation efficiency.
[0023] To address the aforementioned technical problems, embodiments of this application provide a photovoltaic front panel and its preparation method, as well as photovoltaic modules and photovoltaic curtain walls. The substrate of the photovoltaic front panel is coated with a clay slurry formed by mixing nano-clay, thermoplastic resin, and organic solvent on the light-facing side. The clay slurry dries to form a composite scattering film, in which light can undergo volume scattering, thereby achieving a white appearance for the photovoltaic front panel. Compared to surface scattering of light on the surface of a traditional photovoltaic front panel, this reduces optical loss caused by optical reflection, thereby reducing the power generation loss of the photovoltaic module using the photovoltaic front panel. This is beneficial for improving the power generation efficiency of the photovoltaic module, enabling the photovoltaic module to achieve both high decorative appeal and high power generation efficiency.
[0024] For specific details, please refer to... Figure 1 This application provides a method for preparing a photovoltaic front panel, comprising the following steps: Step S1: Disperse nano-clay, thermoplastic resin, and organic solvent in a certain proportion to prepare a clay slurry. In the clay slurry, the volume fraction of the nano-clay is 20% to 80%, the volume fraction of the thermoplastic resin is 15% to 20%, and the remainder is the organic solvent.
[0025] Step S2: Provide a substrate and apply the clay slurry to the light-facing surface of the substrate.
[0026] Step S3: The substrate coated with the clay slurry is dried to obtain a photovoltaic front panel with a composite scattering film formed on the light-facing surface. The brightness of the composite scattering film is 30 to 60, the haze of the composite scattering film is 35% to 95%, and the transmittance of the composite scattering film is 55% to 90%.
[0027] In the photovoltaic front panel prepared by the method described in the embodiments of this application, the substrate is coated with a clay slurry formed by mixing the nano-clay, the thermoplastic resin, and the organic solvent on the light-facing side. The clay slurry is dried to form the composite scattering film. Since the nano-clay dispersed in the thermoplastic resin can form a wave network with a three-dimensional refractive index, light undergoes weak Rayleigh / Mie scattering (i.e., volume scattering) inside the composite scattering film, which only changes the direction of the light path to form haze and a white appearance, with almost no interface reflection and non-absorption loss. Therefore, the white appearance of the photovoltaic front panel can be achieved. Compared with the surface scattering of light on the surface of a traditional photovoltaic front panel, the optical loss caused by optical reflection is reduced, thereby reducing the power generation loss of the photovoltaic module using the photovoltaic front panel. This is beneficial to improving the power generation efficiency of the photovoltaic module, enabling the photovoltaic module to achieve both high decorative effect and high power generation efficiency.
[0028] It is understood that the photovoltaic front panel of this application embodiment achieves its white appearance by relying on the nano-volume scattering characteristics inside the composite scattering film, unlike traditional photovoltaic front panels which rely on surface scattering based on microscopic textures to achieve a white appearance. Therefore, under long-term outdoor wind, sand, ultraviolet, and humid conditions, the photovoltaic front panel of this application embodiment will not darken or yellow due to surface wear, thus greatly improving the durability of the appearance and solving the aging color difference problem of traditional photovoltaic front panels.
[0029] In one embodiment of this application, the process of preparing the clay slurry may specifically involve: first dissolving the thermoplastic resin in a portion of an organic solvent, then adding the nano-clay and replenishing the remaining organic solvent, followed by mixing and dispersing using a combination of high-speed stirring and ultrasonic dispersion. For example, the mixture of the nano-clay, the thermoplastic resin, and the organic solvent can be subjected to high-speed stirring and ultrasonic dispersion using equipment such as an ultrasonic disperser, so that the nano-clay and the thermoplastic resin can be uniformly dispersed in the organic solvent. Thus, after the organic solvent dries and evaporates, the nano-clay can be uniformly dispersed in the thermoplastic resin, which helps to improve the uniformity of light volume scattering within the composite scattering film, thereby improving the uniformity of the white appearance of the photovoltaic front panel and the photovoltaic module.
[0030] Wherein, the organic solvent can be 50% to 80% of the total organic solvent; the stirring speed of the high-speed stirring can be 1000 rpm to 3000 rpm, and the stirring time can be 10 min to 30 min; the frequency of the ultrasonic dispersion can be 20 kHz to 40 kHz, the ultrasonic dispersion time can be 15 min to 60 min, and the ultrasonic dispersion time is not less than the stirring time; the ultrasonic dispersion temperature is room temperature, for example, 20°C to 30°C.
[0031] In one embodiment of this application, the volume fraction of the nano-clay in the clay slurry is preferably 25% to 75%. It is easy to understand that by reasonably limiting the volume fraction of the nano-clay in the clay slurry, on the one hand, it can prevent the volume fraction of the nano-clay from being too high, avoiding an exponential increase in the viscosity of the clay slurry and excessive yield stress, which would be detrimental to coating, ensuring that the clay slurry can be coated onto the substrate. Simultaneously, it can prevent the local enrichment of the nano-clay in the clay slurry, which would lead to stress concentration, increased porosity, or deterioration of interfacial bonding, ensuring the uniformity and stability of the composite scattering film formed during drying. On the other hand, it can prevent the volume fraction of the nano-clay from being too low, avoiding a low content of nano-clay in the composite scattering film, reducing the volume scattering effect on light, and affecting the brightness of the white appearance of the photovoltaic module.
[0032] In one embodiment of this application, before applying the clay slurry to the light-facing surface of the substrate, the light-facing surface of the substrate can be cleaned using equipment such as a plasma cleaner to remove oil stains and dust, which helps to improve the adhesion of the clay slurry to the light-facing surface of the substrate.
[0033] In one embodiment of this application, the thickness of the composite scattering film is 8 μm to 12 μm. By limiting the thickness of the formed composite scattering film within a reasonable range, it is possible to avoid the increased light absorption loss and reduced light transmittance caused by an excessively thick composite scattering film, which would affect the power generation efficiency of the photovoltaic module using the photovoltaic front panel. On the other hand, it is possible to avoid the weak volume scattering effect of the composite scattering film caused by an excessively thin composite scattering film, which would reduce the brightness value of the composite scattering film, and thus reduce the brightness value of the photovoltaic front panel. It should be noted that the brightness, haze, and transmittance values of the composite scattering film are specifically related to the volume fraction of the nano-clay in the clay slurry and whether the surface of the composite scattering film has the multilayer periodic structure described later, which will be described in different embodiments below. More preferably, the thickness deviation of the composite scattering film in different regions can be set to less than 0.5 micrometers. By controlling the thickness deviation of the composite scattering film to be less than a certain threshold, the uniformity of light scattering of the composite scattering film can be ensured, avoiding local over-brightness or under-brightness or scattering angle drift, thus achieving highly consistent surface light source output and ensuring the consistency of the white appearance of the photovoltaic front panel and the photovoltaic module. Of course, in other embodiments of this application, the threshold for the thickness deviation of the composite scattering film in different regions can also be other reasonable values, such as, but not limited to, 0.4 micrometers or 0.3 micrometers, and is not limited thereto.
[0034] In one embodiment of this application, coating the clay slurry onto the light-facing surface of the substrate specifically includes: uniformly coating the clay slurry onto the light-facing surface of the substrate using at least one of a spin coater, slot coater, sprayer, or blade coater. In other words, the clay slurry can be coated onto the light-facing surface of the substrate using any method such as spin coating, slot coater, sprayer, or blade coater; the coating process is simple and low-cost.
[0035] As described above, in the photovoltaic front panel of this application embodiment, the clay slurry achieves good slurry dispersion through high-speed stirring and ultrasonic dispersion, and the clay slurry can be coated with a wide width and uniform film thickness. Therefore, the overall color difference of the photovoltaic front panel can be small, which meets the requirements of large-area integrated decoration of building curtain walls.
[0036] In one embodiment of this application, drying the substrate coated with the clay slurry specifically includes: allowing the organic solvent in the clay slurry to evaporate naturally under room temperature and windless conditions until it is dried and cured. Curing the clay slurry coated on the substrate at room temperature to form the composite scattering film does not require high temperature or high pressure conditions, nor does it require customized molds. It is fully compatible with existing BIPV and photovoltaic module encapsulation production lines, requires no new equipment, has low modification costs, and facilitates the mass production of the photovoltaic front panel and the photovoltaic module.
[0037] Furthermore, in one embodiment of this application, before coating the clay slurry onto the light-facing surface of the substrate, the preparation method further includes: using a magnetron sputtering device or an electron beam evaporation device to alternately deposit Nb2O5 and SiO2 on the light-facing surface of the substrate to form a multilayer periodic structure. In other words, a multi-layered periodic structure consisting of alternating Nb2O5 and SiO2 layers is formed between the light-facing surface of the substrate and the composite scattering film. It is easy to understand that, since the Nb2O5 layer has a high refractive index and the SiO2 layer has a low refractive index, the significant refractive index difference between the Nb2O5 layer and the SiO2 layer can be used to achieve precise light wave modulation. This allows the Nb2O5 layer and the SiO2 layer to selectively reflect the light propagating through the composite scattering film, thereby allowing the reflected light to re-enter the composite scattering film. This, combined with the volume scattering effect of the composite scattering film, achieves light path homogenization, which is beneficial to improving the brightness of the white appearance of the photovoltaic front panel and the photovoltaic module using the photovoltaic front panel. This achieves the goal of obtaining a high-brightness pure white appearance of the photovoltaic module with controllable small absorption loss. It should be noted that the aforementioned multilayer periodic structure refers to a polyelectrolyte multilayer film prepared by electrostatic adsorption layer-by-layer self-assembly technology in an environment where N,N-dimethylformamide (DMF) is used as a solvent or mixed medium; that is, a dielectric multilayer film structure.
[0038] Optionally, the total number of Nb₂O₅ and SiO₂ layers can be from 4 to 10. By limiting the total number of Nb₂O₅ and SiO₂ layers to a reasonable range, the film stress of the multilayer periodic structure can be balanced and absorption loss reduced while meeting optical performance indicators (such as reflectivity). Alternatively, a multi-objective Bayesian optimization algorithm can be used to adjust the thickness of each layer of Nb₂O₅ and SiO₂ with the objectives of maximizing brightness, minimizing optical loss, and achieving color uniformity. In this way, the optimal combination of parameters such as the number of layers in the multilayer periodic structure and the film thickness of Nb₂O₅ and SiO₂ can be quickly determined, achieving intelligent optimization of each parameter, eliminating trial and error, and significantly shortening the R&D cycle.
[0039] In the embodiments of this application, the nano-clay may be, but is not limited to, one or a combination of at least two selected from montmorillonite, kaolin, illite, sepiolite, and optically active clay; and / or, the thermoplastic resin may be, but is not limited to, one or a combination of at least two selected from thermoplastic acrylic resin, polyvinyl chloride, polyetheretherketone, polystyrene, polytetrafluoroethylene, polyether ester, polyurethane, polyvinyl alcohol, polyethylene, polystyrene-butadiene copolymer, polycarbonate, polyvinyl alcohol acetal, modified thermoplastic epoxy resin, and polyimide ester; and / or, the organic solvent may be, but is not limited to, a combination of at least two selected from terpineol, butyl carbitol acetate, butyl carbitol, dibutyl phthalate, benzyl alcohol, diethylene glycol dibutyl ether, diethylene glycol butyl ether, and diethylene glycol butyl ether acetate; and / or, the substrate may be, but is not limited to, one selected from low-iron ultra-clear glass, float glass, patterned glass, textured glass, ultra-clear tempered glass, ultra-clear semi-tempered glass, and transparent polymer substrate. In the embodiments of this application, the nano-clay, the thermoplastic resin, the organic solvent, and the substrate can all be made of materials already available on the market, without the need for special modifications, which helps to reduce manufacturing costs.
[0040] Preferably, in one embodiment of this application, the nanoclay is organically modified montmorillonite, the thermoplastic resin is weather-resistant thermoplastic acrylic resin, and the organic solvent is a mixture of terpineol and butyl carbitol acetate. The nanoclay is natural montmorillonite nanoclay, which is abundant and inexpensive, requiring no expensive special nanomaterials or precision micro-nano processing, resulting in excellent economic efficiency for mass production. Furthermore, the thermoplastic resin and the organic solvent are also low-cost, leading to low overall manufacturing costs for the photovoltaic front panel and facilitating mass production.
[0041] In one possible implementation, the organically modified montmorillonite can be prepared by the following method: dispersing sodium-based montmorillonite in deionized water to form a suspension, wherein the weight ratio of sodium-based montmorillonite to deionized water is 1:20~40; then heating the suspension to 60℃~80℃; stirring the suspension at a stirring speed of 140rpm~900rpm; and slowly adding an organic modifier, such as hexadecyltrimethylammonium bromide, sodium dodecyl sulfonate, or octadecylamine salt, while stirring, wherein the amount of the organic modifier added is 10%~30% of the mass of the sodium-based montmorillonite; maintaining the reaction temperature (i.e., the aforementioned heating temperature) for 2h~4h; and then sequentially performing centrifugation, washing, drying, and grinding processes to obtain the organically modified montmorillonite powder. After organic modification, the interlayer spacing of the sodium-based montmorillonite increases, which is beneficial to improving its compatibility with the thermoplastic resin, and thus facilitates uniform dispersion in the clay slurry. It should be noted that in other embodiments of this application, the organically modified montmorillonite can also be prepared by other known organic modification methods, or commercially available organically modified montmorillonite products can be purchased directly, and there is no limitation in this regard.
[0042] The following will describe, with reference to specific embodiments, several performance indicators of the photovoltaic front panel prepared by the method provided in this application.
[0043] Example 1 In Example 1, the nanoclay is selected as organically modified montmorillonite nanoclay. The thickness of a single layer of the nanoclay can be 1 nm, and the sheet diameter can be 20 nm to 50 nm. The thermoplastic resin is selected as weather-resistant thermoplastic acrylic resin, and the organic solvent is a mixture of terpineol and butyl carbitol acetate. The clay slurry is prepared by this process, and the specific preparation process of the clay slurry can be found in the aforementioned description. In the clay slurry, the volume fraction of the nanoclay is 50%, the volume fraction of the thermoplastic resin is 18%, and the remainder is the organic solvent. The clay slurry is subjected to high-speed stirring and ultrasonic dispersion for a certain period of time, for example, but not limited to 30 minutes, to ensure that no agglomeration occurs in the clay slurry and to ensure that the nanoclay is uniformly dispersed. Then, the clay slurry is applied to the light-facing surface of the low-iron ultra-white glass (i.e., the substrate) using a slit coating method, with a coating thickness of 8 μm to 12 μm; the substrate is then left to dry at room temperature for 15 to 25 minutes to allow the organic solvent to completely evaporate, thereby solidifying the composite scattering film on the surface of the substrate and obtaining the photovoltaic front panel.
[0044] According to experimental calculations, the haze of the composite scattering film in Example 1 is 42%, the transmittance is 88%, and the brightness value is approximately 32. This means that the brightness value of the photovoltaic front panel with the composite scattering film is approximately 32, which is comparable to the brightness value of a traditional photovoltaic front panel using 220-mesh coarse-textured glass. However, the optical loss of the photovoltaic front panel in Example 1 is only 0.9%, and the power generation loss of the photovoltaic module using the photovoltaic front panel is less than 1%, which is far lower than the optical loss (0.95%) caused by the traditional photovoltaic front panel and the power generation loss (6.5%) of the photovoltaic module using the traditional photovoltaic front panel.
[0045] Example 2 In Example 2, unlike Example 1, the volume fraction of the nano-clay in the clay slurry is increased to 75%, while the remaining slurry formulation and preparation process are the same.
[0046] According to experimental calculations, the haze of the composite scattering film in Example 2 is 78%, the transmittance is 72%, and the brightness value is increased to approximately 36. That is, by increasing the volume fraction of the nano-clay in the clay slurry, the brightness value of the composite scattering film and the photovoltaic front panel with the composite scattering film can be further improved, thereby further enhancing the visual whiteness of the photovoltaic front panel. Moreover, the optical loss of the photovoltaic front panel in Example 2 is 1.3%. Although the optical loss is slightly increased, the white appearance of the photovoltaic front panel is further improved, achieving a dual match of high whiteness and low loss.
[0047] Example 3 In Example 3, unlike Example 1, before coating the clay slurry onto the light-facing surface of the substrate, the aforementioned multilayer periodic structure is first prepared on the light-facing surface of the substrate using a magnetron sputtering device. Nb₂O₅ and SiO₂ are deposited alternately, with a preferred total of 6 layers. Bayesian multi-objective optimization is used to optimize the thickness of each layer, aiming to maximize brightness, minimize optical loss, and achieve uniform color. Then, the clay slurry is coated onto the surface of the multilayer periodic structure (i.e., the DMF dielectric multilayer film), and finally dried and cured to obtain the composite scattering film.
[0048] According to experimental calculations, the haze of the composite scattering film in Example 3 is 90%, the transmittance is 60%, and the brightness value is increased to approximately 60. That is, by preparing the multilayer periodic structure composed of alternating deposition of Nb2O5 and SiO2 on the light-facing surface of the substrate, the brightness value of the composite scattering film and the photovoltaic front panel can be further improved, resulting in a further increase in visual whiteness and achieving a high-brightness pure white decorative effect. Moreover, the optical loss of the photovoltaic front panel in Example 3 is 11%. Although the optical loss increases, it is still significantly reduced compared to the optical loss brought about by the traditional photovoltaic front panel pure white solution, and a dual match of high whiteness and low loss is achieved.
[0049] It should be noted that, in the embodiments of this application, the brightness, haze and transmittance of the composite scattering film, the optical loss of the photovoltaic front panel and the power generation loss of the photovoltaic module using the photovoltaic front panel can all be measured by existing technology and corresponding equipment, and will not be elaborated further.
[0050] In summary, the photovoltaic front panel prepared by the method described in this application allows for volume scattering of light within the composite scattering film, achieving a white appearance. Compared to surface scattering of light on the surface of traditional photovoltaic front panels, this method reduces optical losses due to optical reflection, thereby reducing power generation losses in photovoltaic modules using the photovoltaic front panel. This improves the power generation efficiency of the photovoltaic modules, enabling them to achieve both high aesthetics and high power generation efficiency. Furthermore, under long-term outdoor conditions of wind, sand, ultraviolet radiation, and high humidity, the photovoltaic front panel described in this application will not darken or yellow due to surface wear, significantly improving the durability of the appearance and solving the aging and color difference problem present in traditional photovoltaic front panels. Furthermore, by adjusting the volume fraction of the nano-clay in the clay slurry and controlling the film thickness deviation of the composite scattering film, a visual gradient matching from near white to high white can be achieved for the photovoltaic front panel. Further, by combining it with the multi-layer periodic structure (i.e., DMF dielectric multi-layer film), high-brightness pure white can be achieved, thereby enabling the photovoltaic front panel to cover the needs of multiple scenarios such as ordinary residences, commercial curtain walls, and high-end landmarks.
[0051] Furthermore, embodiments of this application also provide a photovoltaic front panel, which is prepared using the photovoltaic front panel preparation method described in any of the above embodiments. The photovoltaic front panel possesses all the beneficial effects of the photovoltaic front panels in any of the foregoing embodiments; more detailed information can be found in the aforementioned related content, which will not be repeated here.
[0052] For further details, please refer to Figure 2The embodiments of this application provide a photovoltaic module 100, including a photovoltaic front panel 1, a first encapsulating film 2, a solar cell 3, a second encapsulating film 4, and a photovoltaic back panel 5, which are laminated together in sequence. The photovoltaic front panel 1 is prepared by the photovoltaic front panel preparation method described in any of the above embodiments.
[0053] The first encapsulating film 2, the solar cell 3, the second encapsulating film 4, and the photovoltaic backsheet 5 can all be corresponding components from existing photovoltaic modules, without limitation or elaboration. It is understood that the photovoltaic front panel 1 in this embodiment achieves a white appearance and reduces optical loss and corresponding power generation loss by forming the composite scattering film on the light-facing surface of the substrate. This does not affect the solar cell 3 layered beneath the photovoltaic front panel 1, thus ensuring perfect compatibility with existing high-efficiency cells such as SHJ silicon heterojunction and TOPCon cells, without damaging the cell passivation structure or increasing leakage current.
[0054] Furthermore, embodiments of this application provide a photovoltaic curtain wall, including the photovoltaic module 100 as described above.
[0055] It should be noted that, similar to existing photovoltaic modules and photovoltaic curtain walls, the photovoltaic module 100 and the photovoltaic curtain wall described in this application embodiment also have other components or structures, which will not be described in detail here.
[0056] In the description of this application, the references to terms such as "embodiment," "specific embodiment," and "example" indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0057] Although embodiments of this application have been shown and described, those skilled in the art will understand that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of this application, the scope of which is defined by the claims and their equivalents.
Claims
1. A method for preparing a photovoltaic front panel, characterized in that, The preparation method includes: Nano-clay, thermoplastic resin, and organic solvent are dispersed in a certain proportion to prepare a clay slurry; wherein, in the clay slurry, the volume fraction of the nano-clay is 20% to 80%, the volume fraction of the thermoplastic resin is 15% to 20%, and the balance is the organic solvent. A substrate is provided, and the clay slurry is coated onto the light-facing surface of the substrate; and The substrate coated with the clay slurry is dried to obtain a photovoltaic front panel with a composite scattering film formed on the light-facing surface. The brightness of the composite scattering film is 30 to 60, the haze of the composite scattering film is 35% to 95%, and the transmittance of the composite scattering film is 55% to 90%.
2. The method for preparing a photovoltaic front panel as described in claim 1, characterized in that, The nano-clay has a volume fraction of 25% to 75% in the clay slurry, and the composite scattering film has a thickness of 8 μm to 12 μm.
3. The method for preparing a photovoltaic front panel as described in claim 1, characterized in that, The nano-clay is one or a combination of at least two of the following: montmorillonite, kaolinite, illite, sepiolite, and optically active clay. And / or, the thermoplastic resin is one or a combination of at least two of the following: thermoplastic acrylic resin, polyvinyl chloride, polyether ether ketone, polystyrene, polytetrafluoroethylene, polyether ester, polyurethane, polyvinyl alcohol, polyethylene, polystyrene-butadiene copolymer, polycarbonate, polyvinyl acetal, modified thermoplastic epoxy resin, and polyimide ester. And / or, the organic solvent is a combination of at least two of the following: terpineol, butyl carbitol acetate, butyl carbitol, dibutyl phthalate, benzyl alcohol, diethylene glycol dibutyl ether, diethylene glycol butyl ether, and diethylene glycol butyl ether acetate; And / or, the substrate is one of the following: low-iron ultra-clear glass, float glass, patterned glass, textured glass, ultra-clear tempered glass, ultra-clear semi-tempered glass, and transparent polymer substrate.
4. The method for preparing a photovoltaic front panel as described in claim 3, characterized in that, The nano-clay is organically modified montmorillonite, the thermoplastic resin is weather-resistant thermoplastic acrylic resin, and the organic solvent is a mixture of terpineol and butyl carbitol acetate.
5. The method for preparing a photovoltaic front panel as described in claim 1, characterized in that, The thickness deviation of the composite scattering film in different regions is less than 0.5 micrometers; And / or, the step of coating the clay slurry onto the light-facing surface of the substrate specifically includes: uniformly coating the clay slurry onto the light-facing surface of the substrate using at least one of a spin coater, a slot coater, a spraying device, and a blade coater. And / or, the drying of the substrate coated with the clay slurry specifically includes: allowing the organic solvent in the clay slurry to evaporate naturally under normal temperature and windless conditions until it is dried and cured.
6. The method for preparing a photovoltaic front panel according to any one of claims 1 to 5, characterized in that, Before coating the clay slurry onto the light-facing surface of the substrate, the preparation method further includes: Using magnetron sputtering or electron beam evaporation equipment, Nb2O5 and SiO2 are alternately deposited on the light-facing surface of the substrate to form a multilayer periodic structure.
7. The method for preparing a photovoltaic front panel as described in claim 6, characterized in that, The total number of Nb2O5 and SiO2 layers is 4 to 10. And / or, using a multi-objective Bayesian optimization algorithm, adjust the thickness of each layer of Nb2O5 and SiO2.
8. A photovoltaic front panel, characterized in that, The photovoltaic front panel is prepared using the photovoltaic front panel preparation method as described in any one of claims 1 to 7.
9. A photovoltaic module, comprising a photovoltaic front panel, a first encapsulating film, solar cells, a second encapsulating film, and a photovoltaic back panel laminated together in sequence, characterized in that, The photovoltaic front panel is prepared using the photovoltaic front panel preparation method as described in any one of claims 1 to 7.
10. A photovoltaic curtain wall, characterized in that, Including the photovoltaic module as described in claim 9.